872-P: Efficacy and Safety of Crisugabalin in Chinese Patients with Diabetic Peripheral Neuropathic Pain and Inadequate Response to Pregabalin—A Phase 2 Randomized Clinical Trial - ZHENG, CHAO; ZHAO, YIMING; LIU, WEI; ZHANG, FANG; XU, NA (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: Most guidelines recommend calcium channel modulators as the initial treatment option for Diabetic Peripheral Neuropathic Pain (DPNP), but there is limited comparative evidence to guide the choice of treatment when patients show inadequate response to one of these modulators. Crisugabalin, a novel third-generation calcium channel modulator, has demonstrated both efficacy and safety in a phase 3 trial. This study aimed to evaluate the efficacy and safety of Crisugabalin in Chinese patients with DPNP who had an inadequate response to Pregabalin. Methods: This multicenter, randomized, double-blind, double-dummy, Pregabalin-controlled phase 2 study included patients aged 18-75 years who had been receiving continuous Pregabalin treatment for over 4 weeks and had an inadequate response (VAS≥60 mm). Subjects were randomized to receive either Crisugabalin (40 mg/day) and Pregabalin (300 mg/day, with a 1- week titration) for a 4-week treatment period. The primary endpoint was the change in VAS from baseline at week 4. Secondary outcomes included changes in ADPS and ADSIS at week 4. AEs were monitored for safety. Results: At week 4, the least squares mean change in VAS from baseline was -14.4 for Crisugabalin (n=44) and -7.1 for Pregabalin (n=46), showing a statistical significant difference in favor of Crisugabalin (P=0.0069). Crisugabalin also demonstrated greater improvements in ADPS and ADSIS compared to Pregabalin. Any-grade TEAEs occurred in 29.5% of subjects receiving Crisugabalin, vs 47.8% of those receiving Pregabalin. Most TEAEs were mild to moderate, with dizziness and somnolence being the most common. These TEAEs were generally self-limiting and did not require additional treatment. Conclusion: In Chinese patients with DPNP who had an inadequate response to Pregabalin, Crisugabalin was superior to Pregabalin in reducing DPNP symptoms and was well tolerated.